Congenital Syphilis in Paraná: a historical series analysis (2012-2021) - Santos, Paola (2023)
To analyze the epidemiological profile of congenital syphilis in Paraná from 2012 to 2021.Observational descriptive epidemiological study, survey type, based on data from theInformation System of Notifiable Diseases available at DataSUS. The number of cases ofcongenital syphilis increased from 19.7 per 10,000 live births in 2012 to 51.4 in 2020. Of the 22regional units, Paranaguá, Pato Branco, and Metropolitana reported the highest prevalence. The diagnosis prevailed in white children of up to 6 days old, resulting in cure after treatment. Ofthe mothers, those with low level of education prevailed. Most cases occurred among pregnantwomen who had prenatal care, but with untreated partners. There is a need for investment inhealth education for pregnant women and continued education for health professionals for the diagnosis, monitoring, and treatment of syphilis in pregnant women and especially in partners.